Students’ Learning in Corona Virus Diseases 2019 (Covid-19) Situation - Eka Sustri Harida (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
Online learning is a learning that support the new era of 4.0 industries. Unfortunately, it happens in the bad condition of situation in Indonesia, not because of the needs of learning. Because of the broad case of Corona Viruses Disease 2019 (Covid-19), the students forced to study using online learning, although they are not ready to use it, they must follow the rules to support their learning becomes run as usual. This writing is in order to explore the confiding of the students in online learning in the Covid-19 situation. The data were taken by taking notes for Whats-App chatting, and analyzed by reading, grouping, and interpreting. After analyzing the data, it found that some students felt unconfident with this kind of learning, some are enthusiastic, and the others felt boring. They hope that this situation can be passed soon, so they can come to class to meet their lovely lecturers and friends. If they need to use online learning, it is in the real situation, safe, and peace, without any worries and fright.